2012
DOI: 10.1111/j.1541-0064.2012.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Engaged acclimatization: Towards responsible community‐based participatory research in Nunavut

Abstract: In this article, we consider the formation of responsible research relationships with Inuit communities from an “outsider” researcher perspective. Cautious not to prescribe what counts as responsible, we draw on research experiences in several Nunavut communities to introduce and explain “engaged acclimatization.” This neologism refers to embodied and relational methodological processes for fostering responsible research partnerships, and is inspired by the significance of preliminary fieldwork in orienting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 75 publications
(178 reference statements)
0
57
0
1
Order By: Relevance
“…Logistical needs within CBPR involve creation of a research team or research partnerships such as development of a research advisory board, determination of roles within the project, such as project leaderships, and developing research standards (Velasquez, Knatterud-Hubinger, Narr, Mendenhall, & Solheim, 2011). Such processes have been described as engaged acclimatization, which was documented as crafting relations, learning, immersion, and activism (Grimwood, Doubleday, Ljubicic, Donaldson, & Blangy, 2012). This communication is fundamental within a CPBR approach; however, critical issues about authorship or acknowledgement within community-based research have been inconsistently applied (Castleden, Morgan, & Neimanis, 2010).…”
Section: Community-based Participatory Research (Cbpr)mentioning
confidence: 99%
“…Logistical needs within CBPR involve creation of a research team or research partnerships such as development of a research advisory board, determination of roles within the project, such as project leaderships, and developing research standards (Velasquez, Knatterud-Hubinger, Narr, Mendenhall, & Solheim, 2011). Such processes have been described as engaged acclimatization, which was documented as crafting relations, learning, immersion, and activism (Grimwood, Doubleday, Ljubicic, Donaldson, & Blangy, 2012). This communication is fundamental within a CPBR approach; however, critical issues about authorship or acknowledgement within community-based research have been inconsistently applied (Castleden, Morgan, & Neimanis, 2010).…”
Section: Community-based Participatory Research (Cbpr)mentioning
confidence: 99%
“…Learning and feedback from this preliminary fieldwork informed subsequent research visits (May, July and November 2010, October 2011); for example, study objectives and methods were adapted to better reflect community interests (i.e. the intrinsic purpose), a local research assistant was identified, and strategies for effectively engaging with Inuit participants and organisations were clarified (Grimwood, Doubleday, Ljubicic, Donaldson, & Blangy, 2012). It was during research visits that Baker Lake residents whom at some point in their lifetimes had directly experienced, lived and/or travelled the Thelon, contributed as participants in the methods described below.…”
Section: Participantsmentioning
confidence: 99%
“…A substantial change from TCPS to TCPS2 was the addition of Chapter 9, which is specifically dedicated to the ethics of research involving Indigenous peoples in Canada (CIHR et al ). Chapter 9 was a constant reference in last year's (2012) Summer Issue of The Canadian Geographer (56:2) (Castleden et al , ; Grimwood et al ; Koster et al ), which focused on Indigenous community‐based participatory research in Canadian geography. The special issue included accounts of the progress made and challenges faced by geographers responding to the ethical requirements of research involving Indigenous peoples in Canada.…”
Section: Introductionmentioning
confidence: 99%